Manajemen Risiko Operasional Pada PT. ABC Dengan Menggunakan Metode FMEA - Suparjo, Suparjo; Rochman, Abdul (JHP17 (Jurnal Hasil Penelitian), 2018)
PT. ABC is one of the manufacturing industry that produced the polyurethane panelThis company needed to concern about its operational management. From the initialidentification known that the company had a problem on production process. This companycouldn’t research their target and also production period which resulted in operationaldiscruption, this research tried to fried tofind the causes, the risk and also the solution in thisresearch are ishikawa diagram and FMEA to determine the highest risk in the productionprocees from  FMEA it can be conduded that there are 2 dominant risk needed to be handledfirst the risk are operator didn’n’t wear PPE (Personal Protective Equipment) and lacked ofconcentration while working.Keywords: Ishikawa diagram, Failure Mode and Effect Analysis